Position Statement from the European Board and College of Obstetrics & Gynaecology (EBCOG): The use of medicines during pregnancy: call for action. (June 2016) - Van Calsteren, Kristel; Gersak, Ksenija; Sundseth, Hildrun; Klingmann, Ingrid; Dewulf, Lode; Van Assche, André; Mahmood, Tahir
Abstract: Less than 10% of medicines approved by the FDA since 1980 have provided enough information as regard risks for birth defects associated with their use[1] . Nevertheless, it is estimated that over 90% of pregnant women take over-the-counter (OTC) or prescription medication[2] . Considering the fact that the use of medication in the period before conception and during lactation can also influence the development of the child, information on the impact of their usage during reproductive life is important for everyone. The lack of clear information on this topic results in situations where life-saving medication is discontinued, withheld or used in a reduced dosage by pregnant women, while on the other hand medicines with (potential) toxic effects are taken. This is unacceptable and it is a major public concern that must be addressed. Currently, Europe lacks a robust and comprehensive information system about medication use in reproductive life (preconception, pregnancy and lactation). In order to improve maternal health, and subsequently the health of our next generation, reliable and up to date information should be made available. It should be readily accessible for both health care providers and women who are considering getting pregnant or who are already pregnant. In order to tackle this gap in public health, this paper describes current knowledge of the use of medicines before and during pregnancy. It calls upon all stakeholders involved in medical care, research and medicine regulation, such as policy makers, regulators and governmental agencies, to take action to protect patients and improve public health.